The degree of practicing the administrative process re-engineering requirements for secondary school principals from the point of view of their collaborators (Journal of the College of Basic Education, 2022)
The current research aimed to identify (the degree of practice of administrative process re-engineering requirements). The current research has been identified with secondary school assistants in Baghdad governorate for the academic year (2018-2019). The research sample consisted of (200) assistants, with (80) male assistants and (120) female assistants , They were chosen from the original community of the assistants of the six directorates of education in the province of Baghdad, which numbered (470) assistants and assistants. The researcher extracted indicators of validity and reliability of the questionnaire. The researcher used a number of statistical methods, including: (One-sample t-test, two independent samples t-test, Pearson's correlation coefficient, Cronbach's alpha equation, chi-square). The statistical package (SPSS) was used. To reach the required results in the research procedures. The current research concluded that there is an average degree for the practice of re-engineering administrative processes for secondary school principals from the point of view of their assistants. There are no statistically significant differences in their views due to the gender variable (males - females) in the practice of secondary school principals